Necessity, the Fundamental Basis of Entrepreneurship Development in Africa: A Survey of Southern Nigeria - Awodun, Muritala; Ajonbadi, Hakeem; Bamkole, Peter (Archives of Business Research, 2024)
Majority of the people in Africa found themselves in the situation that has made poverty a life-long experience. Individuals, communities and government, having realized this, have resorted to ‘self-help’ survival strategies, communal support and intervention efforts by the government, in their efforts to struggle out of the poverty cycle. Most of these efforts have been referred to as qualified to be regarded as entrepreneurial at different scales, whether tiny, micro, small, medium or large. Underscoring the survival strategies of these majority of Africans are entrepreneurship characteristics which this research set out to measure. To answer the question of this research, we conducted a survey of Southern Nigeria to examine the authenticity of the foundational nature of entrepreneurship characteristics in the entrepreneurship development process. Our results reveal that necessity is fundamental to the successful development of entrepreneurship in Southern Nigeria, hence the submission of the research that African entrepreneurship is significantly necessity-based.